Inventive Ways of Teaching Mechanical Systems and Control to Grade 9 Learners with Special Learning Needs (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2024)
Mechanical systems and control are part of the Technology subject strand, which involves gaining knowledge and skills in using various machinery and mechanisms such as gears, belts, chains, elevators, and escalators. Technology teachers need to be familiar with innovative teaching methods for instructing learners with special needs. This study aimed to explore creative teaching strategies for teaching Mechanical Systems and Control to grade 9 learners with special needs in the Capricorn district of Limpopo. A qualitative exploratory case study design and homogenous purposive sampling were employed to select two Technology teachers from two special schools in the Capricorn district. The findings of this study revealed that technology teachers encountered significant challenges in identifying and implementing appropriate creative teaching strategies to deliver the content of Mechanical Systems and Control effectively to learners with special learning needs. The study also indicated that although Technology teachers utilized PowerPoint presentations, narrative discourses, textbooks, and artifacts during instruction, these strategies were not always effective for learners with special learning needs. Consequently, the study recommends that teachers receive comprehensive training on teaching learners with special learning needs, focusing on different pedagogies and methods such as the guided exploration method, technology integration, visualization, and the use of technological artifacts to enhance instruction in Mechanical Systems and Control. These learner-centered methods enable teachers to cater to learners' individual learning needs.